Talking with legislators: Educating the public on the dangers of online gambling - Surbakti, Feliks Prasepta Sejahtera (Community Empowerment, 2025)
The practice of online gambling in Indonesia is increasingly alarming due to its ease of access and massive dissemination through various digital platforms. This practice poses detrimental social and economic impacts, such as financial problems, family breakdown, and psychological disorders, and presents regulatory challenges in its eradication. This community service activity employed socialization and interactive discussion methods involving the community and legislators, aiming to raise awareness about the risks of online gambling and provide information on how to address potential dependence or addiction. Furthermore, this activity presented current data regarding the efforts of the Ministry of Communication and Informatics in cutting off access to online gambling sites. The results of the activity indicated that participants gained a better understanding of the types and risks of online gambling and the necessary steps to take if trapped, as measured by a 70% increase in post-test scores. In conclusion, close collaboration between the community and the government plays a crucial role in combating the growing prevalence of online gambling in Indonesia.